The call centre labour process : a study of work and workers' experiences at Joburg Connect, South Africa - Magoqwana, Babalwa Mirianda (Rhodes University, Faculty of Humanities, Department of Sociology, 2015)
This thesis is an investigation of the call centre labour process focusing on both the way work is organised and experienced by the operators and the management of employee relations inside a local government workplace "“ The City of Johannesburg (COJ) Call Centre. The City of Johannesburg is used to understand labour process dynamics in local government. Johannesburg was recently named the 'World's Second Most Inspiring City' (by Global City Index, 2014) possessing economic and political influence within and around South Africa. Johannesburg is the economic hub of the country, contributing nine per cent to the South African GDP. But it needs to be emphasised that the focus of this thesis is on the labour process rather than the City of Johannesburg. The nature of work in the COJ local government call centre involves answering calls about water, electricity, refuse removal, accounts and other general municipal services. The government's objective was to have a more customer centred service delivery plan in compliance with the Batho Pele (People first) framework (RSA, 1997, White Paper on Local Government). This resulted in a shift in the government 'mantra' and philosophy from viewing Johannesburg residents as customers rather than citizens. This shift from public administration to New Public Management (NPM) has meant the introduction of private sector business principles into public services. This seeks to improve organisational and individual performance to enhance service delivery within South African municipalities. This is also meant to promote responsive and performance management culture. The study uses Labour Process Theory set out in Labour and Monopoly Capital (LMC-1974) by Harry Braverman to argue for the need to contextualise the labour process debate within the socio-political understanding of work in South Africa. In developing the argument about the narrow analysis of public sector call centres based on economic lines I have reviewed literature on call centres which is influenced by Michel Foucault and Harry Braverman to understand the public sector call centre labour process. Inspired by Adesina (2002) and Mafeje (1981) this study uses a 'complementarity' approach to knowledge. This means the local context tends to complement the global trends though not without contradictions within the local context. The case study approach was used for in-depth analysis of the local context through different methods (semi-structured interviews, focus group discussions, observations and survey questionnaires) to collect data from different stakeholders within the City of Johannesburg between 2010 and 2013. The concept of a '(dis)connecting city' is fitting for the COJ as this city connects the rest of Sub-Saharan Africa and South Africa to the world through its commerce and political influence. Based on the challenges experienced in this local government call centre I attempt to show the the politicised nature of the public sector call centre labour process. I use the differential power relations in the frontline between customer and Joburg connect workers to illustrate this point. The lack of emphasis on the politicised nature of public sector call centres within literature is informed by the de-contextualised nature of these call centres. In the end, I argue that public sector call centre labour process is multilayered, contradictory and complicated because of these workers' role as citizens, customers, community members and service providers from a politicised community environment.
Keywords: Johannesburg (South Africa) -- Joburg Connect; Call center agents -- South Africa -- Johannesburg -- Case studies; Work environment -- South Africa -- Johannesburg -- Case studies; Customer services -- South Africa -- Johannesburg -- Case studies; Personnel management -- South Africa -- Johannesburg -- Case studies; Employee morale -- South Africa -- Johannesburg -- Case studies; Employees -- Attitudes -- Case studies; Municipal services -- South Africa -- Johannesburg -- Case studies; South Africa -- Economic conditions -- 1991-; South Africa -- Politics and government -- 1994-; South Africa -- Social conditions -- 1994-